Impact of gender on the career development of female traditional Korean medicine doctors: a qualitative study - Se Eun Chun; Ju Hyun Lee; Ju Eun Lee; Seung Min Kathy Lee; Hyunho Kim (BMJ Open)
Objective This study aims to examine the impact of gender and expected gender roles on the career development of young female traditional Korean medicine (KM) doctors.Design We conducted semistructured interviews to examine the experiences of study subjects regarding early career choices, employment, job performance and career moves, as well as future career aspirations, from the perspective of gender. The transcription was analysed using the Strauss and Corbin constant comparative analysis method.Setting The interview was conducted at a quiet and comfortable place selected by the participants in South Korea.Participants Ten female KM doctors in their 30s participated in the study.Results This study reveals that, initially, the participating female KM doctors were unaware of their gender affecting career decisions. However, after graduation and during employment, female doctors experienced direct discrimination or gender segregation while selecting areas of treatment and specialty; they found that they were preferred to work in paediatrics and dermatology departments than in departments treating musculoskeletal health problems. Furthermore, after entering the workforce, female KM doctors found that their gender significantly affects patient–doctor relationships and life events, such as pregnancy and childbirth require temporary career breaks. In addition, female KM doctors assumed stereotypical gender roles both in the workplace and at home, as well as becoming the main nurturer of their children.Conclusion Gender and stereotyped gender roles affect the overall career planning, career moves and even patient–doctor relationships of female KM doctors. Female doctors were also more likely to experience specific gender roles in the workplace and at home, including both childbirth and childrearing.